Hidradenitis Suppurativa is Associated with Symptoms of Keratoconjunctivitis Sicca - Schargus, Marc; Langhorst, Christine Anna; Joachim, Stephanie; Frings, Andreas; Krause, Kristina; Reifenberger, Julia; Geerling, Gerd; Frings, Verena Gerlinde (Current eye research, 2021)
Hidradenitis suppurativa (HS) and psoriasis vulgaris (PSO) are chronic inflammatory dermatoses in which proinflammatory cytokines, such as IL-17, play a central role. The prevalence of keratoconjunctivitis sicca (KCS) is commonly higher in PSO than in healthy individuals. This study was thus set up to investigate the prevalence of KCS among patients with HS. In a cross-sectional study standardized tear film parameters and symptom-oriented questionnaires (OSDI, SPEED) were analyzed in a total of 71 subjects (HS n = 20, PSO n = 20, healthy controls n = 31). Additionally, IL-17 and MMP-9 in the tear film were analyzed. These parameters were correlated to the clinical severity of the skin disease. PSO patients served as inflammatory control group. There were statistically significant differences in OSDI (p = .003) and SPEED (p ≤ 0.001) between HS and the control group, but not between PSO and controls. For HS, there was a statistically significant correlation between symptoms (OSDI) and the severity of HS according to Hurley stage (p = .023). Tear film concentrations showed significantly increased levels of IL-17 (p = .018), but not MMP-9, in PSO alone compared to the control group. Data show that subjective complaints of KCS may be associated with HS and correlate with the severity of the respective Hurley stage, but do not involve alterations of tear film MMP-9 and IL-17. Clinicians should remain mindful that ocular complications in HS are often more vague than in psoriatic patients, but dry eye symptoms might be detrimental for the patients' quality of life.